Relationship between state, market and society in management and development of science and technology in Vietnam - Ngoc, Ho Sy; Doan, Ta Thi; Long, Pham Hoang; Binh, Tran Thi Thanh (Edelweiss Applied Science and Technology, 2024)
During more than 35 years of implementing the renovation policy, our Party has always researched, tested, and applied industrialization models and strategies suitable to the country’s reality. The mid-term National Delegates Conference of the 7th Party Congress (1994) put forward the viewpoint that industrialization and modernization is a process of fundamental and comprehensive transformation of production, business, service and economic and social management activities from mainly using manual labor to widely using labor based on technology, creating high social labor productivity with the motto "Industrialization must go hand in hand with modernization..., forming spearheads of economic development according to the advanced level of world science and technology" . Document XII of the Party (2016) emphasized: "Strongly develop science and technology, make science and technology truly the top national policy, the most important driving force for the development of modern productive forces and knowledge-based economy" . And most recently, Document XIII of the Party (2021) has shaped the development of science and technology in the direction of: (1) Accelerating the transition from dependent industrial development to innovative creative industry, proactively mastering basic technology in Vietnam; (2) Strongly transforming the industrial economy into a digital economy, based on a knowledge foundation; (3) Breakthrough innovation based on a digital economy. Therefore, determining the legal framework of the State, the "interest" relationship brought by the market and the supervision of the social community is very necessary in the management and development of science and technology today. However, the relationship between the three institutions of the state, the market and society in science and technology development still has many shortcomings that need to be addressed and resolved in conjunction with the goal of developing a green economy, a circular economy, inclusive growth, and rapid and sustainable economic development based on the Fourth Industrial Revolution with digital technology, artificial intelligence, the Internet of Things and big data... which has been and is profoundly changing the global production and economy towards a smarter, more efficient direction with an unprecedentedly fast growth rate.